Clinical presentation, magnetic resonance imaging findings, and outcome of 80 Dachshunds with cervical intervertebral disc extrusion - Violini, Francesca; Tirrito, Federica; Cozzi, Francesca; Contiero, Barbara; Anesi, Simone; Zini, Eric; Toni, Cristina (Frontiers in Veterinary Science, 2024)
IntroductionLarge clinical studies regarding cervical intervertebral disc extrusion (IVDE) in Dachshunds are lacking. This retrospective multicentric study therefore aims to describe the clinical features, magnetic resonance imaging (MRI) findings and outcomes of Dachshunds diagnosed with cervical IVDE.MethodsMedical records of Dachshunds with cervical IVDE were reviewed for signalment, onset of clinical signs, neurological examination, MRI features, treatment and outcome.ResultsEighty Dachshunds were included in the study, mostly ambulatory (55% grade 1 and 33% grade 2) and without nerve root signature (85% of cases) on presentation. Information on coat type was available for 56% of dogs; specifically, 41% were smooth-haired, 9% were long-haired and 6% were wire-haired Dachshunds. There were 29 (36%) neutered female, 27 (34%) male entire, 15 (19%) male neutered and 9 (11%) entire female dogs. The onset of clinical signs was most often >48 h (84%). The most common intervertebral disc space affected was C2-C3 (38%) and foraminal IVDEs were reported in 14% of dogs. A foraminal IVDE was diagnosed in only 25% of dogs presented with nerve root signatures. Most dogs (77.5%) were treated surgically. In this group, a higher body condition score on presentation and a higher mean spinal cord compression ratio calculated on MRI were directly and moderately associated with a longer hospitalization time (r = 0.490 p = 0.005 and r = 0.310 p = 0.012, respectively). The recovery time was longer in dogs with an onset of clinical signs <24 h or 24–48 h compared to those with an onset of clinical signs >48 h (3.1 ± 6.5 days versus 1.6 ± 6.2, p < 0.001) in both medically and surgically treated groups. Data about the outcome was available for 83% of dogs. Eighty percent of the entire population of dogs was considered to have completely returned to normal. There was no association between the therapeutic choice (surgical versus medical management) and the outcome of the dogs included in this study.